[Bisons in a pen] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Bisons in a pen on the La Gloria Estate.
Cataloger's title
Keywords: Livestock; Bison farming -- Trinidad and Tobago; Caroni (1975) Limited